1992
DOI: 10.1159/000243743
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Ventilatory Effects of Two Respiratory Stimulants, Caffeine and Doxapram, in Newborn Lambs

Abstract: Caffeine and doxapram are two respiratory stimulants used in the treatment of apnea in newborns. When used concurrently, these drugs may produce interactive effects on the control of breathing in the newborn. The ventilatory effects of these drugs, given alone or together, were measured during 150 min of drug infusion in two groups of awake lambs 2-5 days old. The first group (n = 5) received a caffeine loading dose of 10 mg/kg followed by a maintenance dose of 0.1 mg/kg/h and incremental doses of doxapram: 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Caffeine has been shown to increase carbon dioxide chemoreceptor responsiveness, increase respiratory muscle performance and generally increase central nervous system excitability. 7981 In the Caffeine for Apnea of Prematurity (CAP) trial, the infants randomized to caffeine therapy had a lower incidence of BPD (36% vs. 47%, adjusted OR 0.64 (0.52–0.78)), as defined by oxygen need at 36 weeks PMA. 82 …”
Section: Risk Factors After Birthmentioning
confidence: 99%
“…Caffeine has been shown to increase carbon dioxide chemoreceptor responsiveness, increase respiratory muscle performance and generally increase central nervous system excitability. 7981 In the Caffeine for Apnea of Prematurity (CAP) trial, the infants randomized to caffeine therapy had a lower incidence of BPD (36% vs. 47%, adjusted OR 0.64 (0.52–0.78)), as defined by oxygen need at 36 weeks PMA. 82 …”
Section: Risk Factors After Birthmentioning
confidence: 99%
“…Although these studies demonstrated the effects of caffeine in the first days after birth, there is little data on the direct effect of caffeine on respiratory effort or whether gestational age (GA) influences the effect of caffeine. Bairam et al (19) showed that in 2-5-day-old term lambs Vt i increased after a loading dose of caffeine. Kraaijenga et al (15) confirmed this in 1-4-day-old preterm infants by measuring diaphragmatic activity after caffeine administration (19).…”
mentioning
confidence: 99%
“…Bairam et al (19) showed that in 2-5-day-old term lambs Vt i increased after a loading dose of caffeine. Kraaijenga et al (15) confirmed this in 1-4-day-old preterm infants by measuring diaphragmatic activity after caffeine administration (19). Within 5 min of administration, diaphragmatic activity increases, resulting in a 30% increase in tidal volumes (15).…”
mentioning
confidence: 99%
“…The caffeine-doxapram combination has been used in only one human study (6). In newborn lambs, ventilation has been reported to increase after a loading dose of caffeine and to increase further with the addition of incremental doses of doxapram (18). Other authors have used aminophylline or theophylline combined with doxapram in premature infants (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…The doxapram-related increase in blood pressure is well known (7,(19)(20)(21)(22). In human studies, surprisingly, it seems that blood pressure was not monitored in all treated infants (8) and blood pressure values were not always reported (5,18). Barrington et al (19), who used doxapram alone, reported an increase in blood pressure at doses Ͼ1.5 mg kg −1 h −1 .…”
Section: Discussionmentioning
confidence: 99%